More than memory (Wheeler Pub, Grand Central Publishing, 2001)
Eight years have passed since their passionate young love went wrong. Now Nelda returns to her Iowa farmland home, only to rediscover her teenage love who was, for a few brief months, her husband. But is their love reawakening?

Hart's Hollow farm (New Americana, 4,, 2022)
Hart's Hollow Farm has seen better days, but for Emmy Hart it is a home worth fighting for. She asks Kristen Daniels to help return the farm to its former glory and Kristen accepts, despite her fears about getting involved with Emmy or the two kids in Emmy's care. Emmy's grandson, Mitch Hart thought he'd kicked the red dust of Georgia off his boots forever. Now haunted by the loss of the sister he couldn't save, he's determined to see his orphaned niece and nephew in a better life out of this small town. Something about Kristen's spirit has Mitch sticking around, and wondering if he's gone a bit crazy himself-- crazy in love. -- adapted from cover.

The enchanted hacienda (Harlequin Audio, Park Row Books, 2023)
Harlow Estrada returns to the enchanted Hacienda Estrada, a family farm in Mexico where her mother, sisters, aunt and cousins harness the magic of charmed flowers, but when she's chosen to watch over the farm, she panics since she, herself, is magic-less, until she opens her heart to love and creativity.

Crime and cherry pits (Farm to table mystery, ,, 2024)
"Shiloh Bellamy can hardly believe it-for the first time in her family farm's seventy-year history, she has managed to score a highly coveted booth at the Cherry Farm Market in Traverse City, Michigan. It's a huge win in her master plan to bring the run-down farm back to life...and the fact that her coup has sent her next-door neighbor and organic farming competitor into fits of jealousy doesn't hurt either. But the festive atmosphere at the farm market takes a dark turn when a man entered in the famous cherry pit-spitting competition chokes and dies. When the death turns out to be more suspicious than a cherry pit down the wrong pipe, Shiloh finds herself under local law enforcement's microscope. And when they discover her cousin Stacey had been secretly dating the man in question-and that he was married to someone else-Shiloh begins to worry that everything she has worked so hard to accomplish with her family's farm is about to be taken away. It will take all her investigative skills, a tenuous friendship (or is it something more?) with the local sheriff, and some help from Shiloh's trusty pug, Huckleberry, to prove the cops are barking up the wrong cherry tree and put the real killer behind bars for good"--

A thousand acres (Recorded Books, Inc., Alfred A. Knopf, Knopf Doubleday Publishing Group, 1996)
PULITZER PRIZE WINNER • NATIONAL BESTSELLER • A "powerful and poignant" twentieth-century reimagining of Shakespeare’s King Lear (The New York Times Book Review) that takes on themes of truth, justice, love, and pride—and centers on a wealthy Iowa farmer who decides to divide his farm between his three daughters.  When the youngest daughter objects, she is cut out of his will. This sets off a chain of events that brings dark truths to light and explodes long-suppressed emotions. Ambitiously conceived and stunningly written, A Thousand Acres reveals the beautiful yet treacherous topography of humanity. “A family portrait that is also a near-epic investigation into the broad landscape, the thousand dark acres of the human heart.... The book has all the stark brutality of a Shakespearean tragedy.” —The Washington Post Book World

A girl's guide to the Outback (Thomas Nelson, Center Point Large Print, 2020)
"Samuel Payton is a passionate youth pastor in Virginia, but below the surface, he's still recovering from the blow of a failed business and insecurities he can't shake. His coworker, start-up expert Kimberly Foster, is brilliant, fearless, and capable, but years of personal rejection have left her defensive and longing for a family. Two people have never been more at odds -- or more attracted to one another. And every day at work, the sparks sure do fly. When Kimberly's ambitious plans for Sam's ministry butt up against his risk-averse nature, Sam decides that obligations to family trump his work for the church. He quits the ministry and heads home to Australia to help his sister, Jules, save her struggling farm. As Kimberly's grand plans flounder, she is forced to face the truth: that no one can replace Sam. Together they strike up a deal: if Kimberly comes to work on Jules's dairy farm and lends her business brains to their endeavor, then maybe -- just maybe -- Sam will reconsider his future with the church"--Provided by publisher.

Farm to trouble (Farm to table mystery, 1,, 2021)
"First in a new series! Shiloh Bellamy cashed in her big city job and 401K to return home to Michigan to save the family farm, but turning Bellamy Farms into a sustainable, organic operation is no small feat. Especially when her new investor is found dead at the farmers market not long after the contract is signed, a contract that the whole town knows her father was wholeheartedly against. Now, Shiloh must clear her family's name and track down the real killer before her farm dreams wilt before her very eyes. But with her father trying to stop any progress on his land, her cousin belittling her every effort, and the whole town believing her family at fault, Shiloh has to carry the investigation on her shoulders or risk all her dreams drying up before they begin" --

Lone Oaks Crossing (New Americana, ,, 2024)
"Set against the vibrant state of Kentucky, a Derby-winning horse trainer strives to reinvent her family's struggling farm -- with the help of a handsome investor."--Publisher's description.